Relationship of Patient Characteristics with Medication Adherence in Type 2 DM - Esri Rusminingsih; Romadhani Tri Purnomo (Indonesian Journal of Global Health Research, 2022)
Indonesia is predicted to have the seventh-highest number of people with type 2 DM worldwide in 2030. Consistent adherence to taking medication as prescribed is the key to diabetes self-care. Poor treatment adherence is associated with poor glycemic control, microvascular and macrovascular complications, and increased care costs. Treatment success is influenced by patient adherence to treatment which is a major factor in therapy outcomes. Objective to identify the relationship between patient characteristics and adherence to medication for patients with type 2 diabetes.This type of research is an analytic observational study with a cross-sectional approach. The samples used were 126 patients who were taken using a purposive sampling technique according to the inclusion criteria: being diagnosed with type 2 diabetes mellitus and receiving a prescription for antidiabetic drugs. The medication adherence instrument used the Morisky Medication Adherence questionnaire (MMAS-8). Data were analyzed using descriptive statistics and the Kendal-tau test. Adherence to taking medication in patients with Type 2 DM was mostly moderate (54%). There was a significant relationship between age (p=0.043), education level (p=0.000), gender (p=0.008), duration of suffering from Type 2 DM (p=0.000), frequency of taking medication (p=0.001), comorbidities (p=0.000), with adherence to taking DM medication. Still, there was no significant relationship between work type and adherence to DM medication (p=0,333). Type 2 DM patients mostly have a moderate level of medication adherence. Medication Compliance in Patients with Type 2 DM is influenced by several factors, including age, gender, education level, duration of suffering from DM, number of drugs taken, frequency of medication, and comorbidities.